Rice (Oryza sativa L.) blast resistance genes bioinformatic analysis - К. В. Бондаренко; Г. І. Сліщук; Н. Е. Волкова (Plant Varieties Studying and Protection)
Purpose. To investigate rice blast resistance genes polymorphism by using bioinformatic methods.